Left to dry: unseen risks lurking on reusable medical devices - Terra A. Kremer; Gerald McDonnell; Jamie Fogarty; Cindy Rodriguez; Christopher H. Ratanski; Neil J. Rowan (Scientific Reports)
Abstract In this study, the intricate relationship between the complexity of reusable medical devices and their cleaning efficacy is explored to the point of cleaning failure. The results identified complex device features that require manual cleaning regardless of soil drying time, as well as device designs (i.e., features) that are appropriate for a fully automated cleaning process. All features were evaluated for cleaning performance under conditions where the soil was not allowed to dry, as well as replacing manual cleaning steps with non-manual methods, (i.e., substituting manual brushing and flushing with soaking and sonication). Findings revealed that soil drying on reusable medical devices can increase the cleaning challenge specific to the device feature. Devices engineered with visually accessible challenging geometries, as opposed to those with enclosed or concealed features, successfully met the requirements for soil drying times and semi-automated cleaning evaluations. However, device features with occluded geometries such as ball bearings, leaf springs, threaded screws, and mated surfaces proved more challenging to clean effectively. Since device features vary in their cleaning complexity, each device should be assessed based on their features. By recognizing the risks associated with soil drying on reusable devices, healthcare facilities can implement appropriate practices that streamline more effective cleaning processes that will inform patient safety along with paving the way for future automation.